Post-Viral Myalgia and The Scope of Homoeopathic Interventions: A Review of Clinical Outcomes - Pareek, Arpana Sandeep; Patil, Sunil Raghunath; Thakare, Rohini Anil; Sharma, Shalini Mukhdeoprasad; Roy, Sharmila; Potdar, Minakshi Ashok (Journal of Neonatal Surgery, 2025)
Background: Post-viral myalgia is a commonly observed sequela following viral infections, including influenza, dengue, and COVID-19. Characterized by persistent muscle pain and fatigue, it often remains a therapeutic challenge. Homeopathy, with its individualized and holistic approach, may offer symptom relief in such chronic conditions. This study aims to evaluate the role of homeopathic medicine in the management of post-viral myalgia. Objectives: To assess the effectiveness of individualized homeopathic treatment in alleviating symptoms of post-viral myalgia and improving patient quality of life. Methods: A prospective observational study was conducted over six months on 20 patients diagnosed with post-viral myalgia. Each patient received individualized homeopathic remedies based on totality of symptoms. Assessment was done using a Visual Analog Scale (VAS) for pain and Fatigue Severity Scale (FSS) at baseline, 4 weeks, and 8 weeks. Improvement was categorized based on percentage change in scores. Results: Out of the 20 patients enrolled in the study, 17 patients (85%) showed significant improvement in muscle pain, with a mean reduction of 62% in Visual Analog Scale (VAS) scores by the end of 8 weeks. Fatigue Severity Scale (FSS) scores improved in 15 patients (75%), indicating substantial relief from post-viral fatigue and improved ability to perform daily activities. No adverse effects or aggravations were reported during the treatment period, and all patients completed the follow-up. The most commonly prescribed homeopathic remedies included Rhus Toxicodendron, Gelsemium sempervirens, Arnica montana, Phosphoric acid, Bryonia alba, Sarcolactic acid and Lycopersicum. Conclusion: Homeopathic medicine may be a safe and effective therapeutic option in managing post-viral myalgia. The individualized approach offers potential benefits in symptom control and quality-of-life enhancement. Larger randomized controlled trials are recommended to further validate these findings.